Role of rare-earth elements in enhancing bioelectrocatalysis for biosensing with NAD+-dependent glutamate dehydrogenase. Issue 40 (23rd September 2021) - Guan, Lihao; Wu, Fei; Ren, Guoyuan; Wang, Jialu; Yang, Xiaoti; Huang, Xiaohua; Yu, Ping; Lin, Yuqing; Mao, Lanqun
Abstract : This study demonstrated that REEs serve as allosteric promoters for bioelectrocatalysis of glutamate dehydrogenase by triggering subtle reorientation of peptide segments, consequently expediting phase coupling along with the catalytic scheme. Abstract : Dehydrogenases (DHs) are widely explored bioelectrocatalysts in the development of enzymatic bioelectronics like biosensors and biofuel cells. However, the relatively low intrinsic reaction rates of DHs which mostly depend on diffusional coenzymes ( e.g., NAD + ) have limited their bioelectrocatalytic performance in applications such as biosensors with a high sensitivity. In this study, we find that rare-earth elements (REEs) can enhance the activity of NAD + -dependent glutamate dehydrogenase (GDH) toward highly sensitive electrochemical biosensing of glutamate in vivo . Electrochemical studies show that the sensitivity of the GDH-based glutamate biosensor is remarkably enhanced in the presence of REE cations ( i.e., Yb 3+, La 3+ or Eu 3+ ) in solution, of which Yb 3+ yields the highest sensitivity increase ( ca. 95%). With the potential effect of REE cations on NAD + electrochemistry being ruled out, homogeneous kinetic assays by steady-state and stopped-flow spectroscopy reveal a two-fold enhancement in the intrinsic reaction rate of GDH by introducing Yb 3+, mainly through accelerating the rate-determining NADH releasing step during the catalytic cycle. In-depth structural investigations using small angle X-ray scattering and infrared spectroscopy indicate that Yb 3+ induces the backbone compaction of GDH and subtle β-sheet transitions in the active site, which may reduce the energetic barrier to NADH dissociation from the binding pocket as further suggested by molecular dynamics simulation. This study not only unmasks the mechanism of REE-promoted GDH kinetics but also paves a new way to highly sensitive biosensing of glutamate in vivo .